Community Services as the Effort to Develop a Marketing Strategy of Innovative Shellfish Processed Product in Bluru Kidul Village, Sidoarjo - H. Suksmawati; A. Masruhin; A. Kusuma (Nusantara Science and Technology Proceedings)
The indigenous people of Bluru Kidul Village, Sidoarjo, are mostly employed as fishermen. Shellfish become abundant local potential obtained by fishermen. Often, the shells that they obtained are only sold directly to the market which had relatively low prices. Only slightly of women fishermen who process the shellfish to become food products that have a higher selling value. Some of the obstacles faced by them are the lack of confidence in the product that she made and the knowledge of how to market it. To overcome these problems, Universitas Pembangunan Nasional "Veteran" Jawa Timur, through community service activities in the form of community service programs/kuliah Kerja nyata, provide training dan assistance to women fishermen in Bluru Kidul Village, Sidoarjo. The output of these activities is training on the development of innovative shellfish processed products as well as the marketing strategy, which includes making labels and attractive packaging.